Executive Committee Minutes 2013-04-18 - Academic Senate:::::::::
Agenda approved. Minutes of 4/4/13 approved. Chair Report. Revision/reduction from 124 to 120 units for the KIN major approved for Senate consent calendar. Provost Report. Vice President of Administration and Finance Report. Revision/reduction from 124 to 120 units for the CS major approved for Senate consent calendar. President Report. Resolution on Student Unit Load during Summer School and Winter Intersession referred to SAC and EPC. Statewide Senator Report. Vice Chair Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Student Report. Senate agenda approved.